Designing Formulation Strategies for Enhanced Stability of Therapeutic Peptides in Aqueous Solutions: A Review - Primawan Putra Nugrahadi; Wouter L. J. Hinrichs; Henderik W. Frijlink; Christian Schöneich; Christina Avanti (MDPI AG, 2023)
Over the past few decades, there has been a tremendous increase in the utilization of therapeutic peptides. Therapeutic peptides are usually administered via the parenteral route, requiring an aqueous formulation. Unfortunately, peptides are often unstable in aqueous solutions, affecting stability and bioactivity. Although a stable and dry formulation for reconstitution might be designed, from a pharmaco-economic and practical convenience point of view, a peptide formulation in an aqueous liquid form is preferred. Designing formulation strategies that optimize peptide stability may improve bioavailability and increase therapeutic efficacy. This literature review provides an overview of various degradation pathways and formulation strategies to stabilize therapeutic peptides in aqueous solutions. First, we introduce the major peptide stability issues in liquid formulations and the degradation mechanisms. Then, we present a variety of known strategies to inhibit or slow down peptide degradation. Overall, the most practical approaches to peptide stabilization are pH optimization and selecting the appropriate type of buffer. Other practical strategies to reduce peptide degradation rates in solution are the application of co-solvency, air exclusion, viscosity enhancement, PEGylation, and using polyol excipients.